Peran Model Pembelajaran Blended Learning Terhadap Motivasi Belajar Siswa Di sekolah Kristen - Kristina, Ariana; Arifianto, Yonatan Alex; Triposa, Reni (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2023)
This study explores the effectiveness of blended learning model in enhancing students' learning motivation in Christian schools. The blended learning model, which integrates face-to-face and online learning, is recognised as a relevant pedagogical approach to encourage active participation and improve learning quality. This study aims to analyse the effect of blended learning model on students' skills and understanding in Christian schools. The results show that the implementation of blended learning model is positively correlated with the improvement of students' learning outcomes, both in academic aspects and the development of skills and understanding. The findings suggest that blended learning is an effective learning strategy in improving students' learning motivation in Christian schools, by encouraging active participation and comprehensive skill development.Â  This research is expected to be a reference source for educators in developing innovative learning strategies and motivating students to achieve optimal learning outcomes.